Autonomic neuropathy in acute intermittent porphyria. Issue 10 (October 1985) - Laiwah, A C; Macphee, G J; Boyle, P; Moore, M R; Goldberg, A
Abstract : Autonomic function was assessed in subjects with acute intermittent porphyria and age- and sex-matched controls using five different bedside tests of cardiovascular reflexes. During the acute attack both parasympathetic and sympathetic tests were impaired, but subsequently improved during remission. Early parasympathetic dysfunction was also detected during remission and in latent asymptomatic acute intermittent porphyria.